Nivolumab in patients with relapsed or refractory peripheral T-cell lymphoma: modest activity and cases of hyperprogression. Issue 6 (24th June 2022) - Bennani, N Nora; Kim, Hyo Jin; Pederson, Levi D; Atherton, Pamela J; Micallef, Ivana N; Thanarajasingam, Gita; Nowakowski, Grzegorz S; Witzig, Thomas; Feldman, Andrew L; Ansell, Stephen M
Abstract : Peripheral T-cell lymphomas (PTCL), a heterogeneous group of mature aggressive non-Hodgkin's lymphomas, carry a worse prognosis for most subtypes when compared with their B-cell counterparts. Despite recent approval of newer therapies, the outlook for patients with relapsed/refractory (RR) PTCL remains poor and new treatment strategies are clearly needed. Targeting the profoundly immunosuppressive tumor microenvironment in PTCL is one such approach. To determine whether immune checkpoint blockade targeting program death receptor 1 would be effective in PTCL, we conducted an investigator-initiated phase 2 prospective study of single-agent nivolumab for RR PTCL. We report here results of the pre-specified interim analysis. Methods: The primary objective was to assess the overall response rate (ORR). Secondary objectives were to assess safety and tolerability of nivolumab in PTCL and to assess progression-free survival (PFS), duration of response (DOR) and overall survival (OS). Hyperprogressive disease (HPD) was defined as time-to-treatment failure of less than or equal to one month from initiation of therapy. Results: Twelve patients who received at least one cycle of nivolumab were included in this interim analysis. Half (6/12) of the patients had angioimmunoblastic T-cell lymphoma (AITL), 3/12 had PTCL, not otherwise specified. Most (11/12) were advanced stage, had extranodal disease (97.1%) and had received a prior autologous stem cell transplant (50%). The ORR was 33% (95% CI: 12.3 to 63.7%) with two complete response and two partial response. The median PFS was however short at 2.7 months (95% CI: 1.5 to NE); and the median OS was 6.7 months (95% CI: 3.4 to NE). The median DOR was also short at 3.6 months (95% CI: 1.9 to NE). HPD occurred in four patients, three of whom had AITL. Observed grade 3 and higher adverse events (AEs) were non-hematologic in 5/12 (42%), while hematologic AEs were seen in 3/12 (25%). Conclusions: Nivolumab had modest clinical activity in R/R PTCL. Due to a high number of hyperprogression and short DOR, a decision was made to halt the study. These findings likely reflect the distinct biology of PTCL and should be considered when designing future studies using checkpoint inhibitors in these diseases. Trial registration number: NCT03075553 .